Does physical fitness affect cognitive functions differently across adulthood? An advantage of being older - Gajewski, Patrick D.; Golka, Klaus; Hengstler, Jan G.; Kadhum, Thura; Digutsch, Jan; Genç, Erhan; Wascher, Edmund; Getzmann, Stephan (Frontiers in Psychology, 2023)
Introduction There is a large interindividual variability in cognitive functioning with increasing age due to biological and lifestyle factors. One of the most important lifestyle factors is the level of physical fitness (PF). The link between PF and brain activity is widely accepted but the specificity of cognitive functions affected by physical fitness across the adult lifespan is less understood. The present study aims to clarify whether PF is basically related to cognition and general intelligence in healthy adults, and whether higher levels of PF are associated with better performance in the same or different cognitive functions at different ages. Methods A sample of 490 participants (20–70 years) was analyzed to examine this relationship. Later, the sample was split half into the young to middle-aged group (YM; 20–45 years; n = 254), and the middleaged to older group (MO; 46–70 years; n = 236). PF was measured by a quotient of maximum power in a bicycle ergometry test PWC-130 divided by body weight (W/kg), which was supported by a self-reported level of PF. Cognitive performance was evaluated by standardized neuropsychological test batteries. Results Regression models showed a relationship between PF and general intelligence (g-factor) and its subcomponents extracted using structural equation modeling (SEM) in the entire sample. This association was moderated by age, which also moderated some specific cognitive domains such as attention, logical reasoning, and interference processing. After splitting the sample into two age groups, a significant relationship was found between cognitive status, as assessed by the Mini Mental State Examination (MMSE), and PF in both age groups. However, apart from cognitive failures in daily life (CFQ), no other association between PF and specific cognitive functions was found in the YM group. In contrast, several positive associations were observed in the MO group, such as with selective attention, verbal memory, working memory, logical reasoning, and interference processing. Discussion These findings show that middle-aged to older adults benefit more from PF than younger to middle-aged adults. The results are discussed in terms of the neurobiological mechanisms underlying the cognitive effects of PF across the lifespan. Clinical trial registration: https://clinicaltrials.gov/ct2/show/NCT05155397, identifier NCT05155397.